Scaling Orchestration in Physical Model Test of Oscillating Buoy Wave Energy Converter - Qiao, Dongsheng; Zhi, Guangning; Liang, Haizhi; Ning, Dezhi; Yan, Jun; Li, Binbin (Frontiers in Marine Science, 2021)
The physical model test interlinks the concept design and sea trial during the commercial utilization of wave energy converter. Aiming at the oscillating buoy wave energy converter, the energy conversion principle is firstly decomposed. Then, the model scale requirement of fluid motion and corresponding hydrodynamic similarity criterion considered in the physical model test are introduced. Finally, the solution of scaling orchestration problem is proposed considering the overall model scale in different energy conversion processes. The hydrodynamic similarity criterion is selected based on the working mechanism of the energy-capturing body only in contact with water, and the model scale requirements during the other stages of energy conversion structure are determined by the main mechanical factors. The first-stage energy conversion of device is recommended to meet the Froude similarity requirements, while the second-stage and third-stage energy conversions only need to meet the power similarity requirements. The power scale ratio in the three energy conversions is recommended to be consistent with the Froude similarity, and there are none requirements of geometric shape of second-stage and third-stage energy conversions to meet the similarity criteria.